Identification of lipase inhibitor from orthosiphon stamineus benth and analysis of lipase-inhibitor complex interaction - Alias, Norsyuhada (2016)
Natural products are a vast source of potential compounds that can be developed as an anti-obesity agent. One of the mechanisms of anti-obesity agents is inhibition of pancreatic lipase. Orlistat is the only commercial pancreatic lipase inhibitor with FDA approval, but it is derived synthetically and has side effects. Hence, there is a need to find for alternative from natural resources. It is postulated that lipase inhibitor from local plants could change pancreatic lipase structure conformation and impair it function. Therefore, this study aims to screen selected plants for pancreatic lipase-inhibitory activity, to identify the lipase-inhibitory compound and to analyse the lipase-inhibitor complex interaction. Screening of 24 crude extracts for their in vitro activity against porcine pancreatic lipase (PPL) detected four extracts demonstrating high (>70%) inhibition, while seven extracts had medium (30-70%) inhibition and the remaining 13 extracts exhibited low (<30%) inhibition when incubated with PPL at a final concentration of 500 μg/ml for 10 min at 37°C. P. niruri extract displayed the most potent PPL inhibitor, followed by O. stamineus, M. paniculata and A. bilimbi with the IC50 value of 27.7<34.7<41.5<55.2 μg/ml,respectively. The best two extracts, namely P. niruri and O. stamineus, showed noncompetitive and uncompetitive inhibition,respectively. P. niruri and O.stamineus showed total phenolic content of 431.0 ± 0.01 and 103.0 ± 0.01 mg GAE/g dry extract, while total flavonoid content of 14.8 ± 0.07 and 21.6 ± 0.03mg QE/g dry extract, respectively. Both P. niruri and O. stamineus extracts showed high antioxidant activity, with EC50 values of 8.4 and 26.3 μg/ml,respectively. Isolation of lipase-inhibitory compound from P. niruri and O.stamineus was performed via chromatographic approaches. However, the isolation process later came to focus on O. stamineus active fractions due to difficulty separating the P. niruri active fraction. A combined fraction of MK38 and MK39 from O. stamineus extract demonstrated the highest inhibitory activity with 50% PPL inhibition. Fractionation of combined fraction MK38 and MK39 by high-performance liquid chromatography (HPLC) yielded an active compound designated as sub-fraction P5 with 45% PPL inhibition. Sub-fraction P5 was authenticated as rosmarinic acid by spectroscopic analyses, namely liquid chromatography-mass spectrometry-mass spectrometry (MS-MS),Fourier transform infrared spectroscopy (FTIR), and nuclear magnetic resonance (NMR). Rosmarinic acid inhibited PPL in a non-competitive manner with an IC50 value of 19.5 μg/ml. Circular dichroism analysis showed a conformational change of the PPL secondary structure upon binding of rosmarinic acid towards PPL. However, no diffraction data were acquired from X-ray crystallography technique. Molecular docking predicted the potential binding site of rosmarinic acid was positioned far from the active site, whereas a molecular dynamic simulation projected that the flexibility of PPL structure would be affected upon binding of rosmarinic acid towards PPL. Hence, the In silico results were in agreement with the inhibition mode analysis. These results have suggested that rosmarinic acid from O. stamineus may play a complimentary role in obesity treatment, acting as a non-competitive pancreatic lipase inhibitor.